2015
DOI: 10.1038/pr.2015.236
|View full text |Cite
|
Sign up to set email alerts
|

Post-weaning high-fat diet accelerates kidney injury, but not hypertension programmed by maternal diabetes

Abstract: Background:The aim of this study was to establish the underlying mechanisms by which a post-weaning high-fat diet (HFD) accelerates the perinatal programming of kidney injury occurring in the offspring of diabetic mothers. Methods: Male mice, offspring of nondiabetic and diabetic dams were fed with normal diet (ND) or HFD from 4 to 20 wk of age. Rat renal proximal tubular cells were used in vitro. results: On ND, the offspring of dams with severe maternal diabetes had an intrauterine growth restriction (IUGR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 44 publications
3
32
0
Order By: Relevance
“…Consistent with previous reports [30,31], male offspring exposed to post-weaning HF showed glomerulosclerosis, segmental necrosis, thickening in the basal membrane of glomeruli and tubules, dilatation in glomerular capillaries, and tubular dilatation (Figure 3A). Maternal and post-weaning HF were associated with greater degrees of glomerular (Figure 3B, P pre = 0.03 and P post = 0.007) and tubulointerstitial injury (Figure 3C, P pre = 0.005 and P post = 0.005) in male offspring kidneys than those in females.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous reports [30,31], male offspring exposed to post-weaning HF showed glomerulosclerosis, segmental necrosis, thickening in the basal membrane of glomeruli and tubules, dilatation in glomerular capillaries, and tubular dilatation (Figure 3A). Maternal and post-weaning HF were associated with greater degrees of glomerular (Figure 3B, P pre = 0.03 and P post = 0.007) and tubulointerstitial injury (Figure 3C, P pre = 0.005 and P post = 0.005) in male offspring kidneys than those in females.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with previous reports showing fibrotic and epithelial-to-mesenchymal transition (EMT) markers were augmented by HF intake [30,31,37], we found that maternal and post-weaning HF increased mRNA expression of collagen I and α-SMA in the offspring kidneys of both sexes. Noteworthy, male offspring exposed to maternal plus post-weaning HF showed greater degrees of glomerular and tubulointerstitial injury and worse renal function compared to females.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[1][2][3] Lately, high-fat diet (HFD)-induced inflammatory responses in the peripheral tissues, especially in liver, cardiac muscle, and kidney, have been well characterized. [4][5][6] In a previous research, HFD was found to be capable of causing 3 CKD, a progressive loss in renal function over a period of months or years, has been regarded as a threat to people all over the world. 7,8 As the final manifestation of CKD, renal fibrosis is a common pathway toward kidney failure.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, oxidant stress plays a critical role in 308 glomerular dysfunction. Along with chronic inflammation, CD36 may facilitate the development 309 of oxidant stress in LN (Hua et al 2015, Kennedy et al 2013, Aliou et al 2016. 310 Podocyte is most susceptible to injury among the component of the glomerulus and its injury 311 leads to glomerular dysfunction in various renal diseases including LN.…”
mentioning
confidence: 99%